A Review of: College Disrupted: The Great Unbundling of Higher Education - Al-Hattab, Amira Ali (Journal of Educational and Psychological Sciences, 2019)
The writer believes that higher education is facing a big leap with the increasing size of the intranet in education,and the only way - in the writer's opinion - to stay in the field of higher education is to keep up with this change by dismantlingthe traditional system of higher education. The book also discusses the apparent imbalance in the American higher education system- in the opinion of writer Ryan Craig - and what education should be compared to what it is now, comparing the book betweenthe major universities that have endowments and those who do not have a standstill and compete in the field of higher educationand seeks to be Similar to Harvard and elite universities. He believes that the American education system should establisha two-tier system: Harvard and its counterparts benefit from elite students, and a cheaper system harnesses the Internet and technologyto benefit the rest of the students. So that they can get paid for what they pay instead of paying huge tuition fees going to supporta university that does not benefit them and buildings that do not enhance their learning. In the opinion of the writerthat the motivation to address this type of education is the widespread increase in the spread of the Internet and the huge costs requiredby education in its traditional form, which necessitates finding a solution to these problems and changes in the market of higher education.
Keywords: book; writer; rayen kreg; dismantling faculties